Health activity in the context of the sense of coherence and self-esteem of participants of specialised training - Dębska, Urszula; Kałwa, Małgorzata; Juszkiewicz, Anna; Guła-Kubiszewska, Halina (Journal of Education, Health and Sport, 2016)
What can be observed is a growing awareness of personal care about one’s own health and increased physical activity. It influenced by numerous external and internal factors, analysed by researchers of Exercise Psychology. Self-esteem and sense of coherence are some of the most significant factors. Aim: Our study comprised 41 participants of specialised health training 2015–16: diagnosing chosen psychological determinants of participation in this type of activity. Health behaviours of the participants were analysed in the context of the psychological variable of the sense of coherence and sel-esteem. Methods: health training, questionnaires: IZZ, SOC-29, SES, Survey Results: Training participants more frequently declared taking up diverse health behaviours. Comparing the group of training participants with non-training persons we found statistically significant differences in the general level of intensification of health behaviours (t-Student 3,06***) and in sub-scales: Active relaxation in the open (2,69*) and Improvement of fitness by sport (4,23**). The persons with higher self-esteem declared using a significantly higher number of diverse health behaviours (0,62***). The training participants with higher sense of meaningfulnessand sense of comprehensibilitysignificantly more frequently declared taking up health activity (r=0,32*).